Science and technology parks and their heterogeneous effect on firm innovation - Antón Tejón, Marcos; Barge-Gil, Andrés; Martínez, Catalina; Albahari, Alberto (My University, 2024)
Science and Technology Parks (STPs) have proliferated in many countries as an innovation policy tool. Previous studies have mostly used a homogeneous approach, leading to mixed results. This paper aims to explore whether there are factors which generate heterogeneous STP effects on the quality of patents filed by tenants. Creating a novel database of Spanish patents generated on- and off-park, merged with firm and STP characteristics, we find that younger and larger firms benefit more from being on-park and younger and older STPs generate a higher effect on tenants’ patent quality, while STPs promoted by universities exhibit a lower effect.
Keywords: Parques empresariales - Congresos; Science and Technology Parks; Innovation policy; Heterogeneity; Patents